Divine power, justice, and reconciliation - Vorster, Nico (Stellenbosch Theological Journal, 2024)
This contribution seeks to provide a plausible answer to the question as to whether the biblical concepts of justice and reconciliation are compatible with the notion of an omnipotent God. Justice presupposes conditions of injustice, while reconciliation presupposes situations of enmity. This give rise to questions about theodicy: If God is an omnipotent and good being, why would he in the first place have allowed a dysfunctional situation where injustice and enmity could enter creation? The question is dealt with in three sections. The first evaluates answers provided by divine self-limitation theory and the opposing secundae causae theory. I point out that these theories show serious shortcomings. Section 2 reflects on divine power from a philosophical, theological, and biblical perspective. I argue that omnipotence does not mean that God possesses a capacity to act in logically impossible ways. Moreover, omnipotence is a non-necessary attribute of God. God is not a prisoner of his power but can limit and retake his power whenever he wants to. Section 3 deals with the relation between divine power, justice, and reconciliation. I argue that the topic of divine power must be approached through a trinitarian lens that understands God’s attributes in terms of his ad intra perichoretic communion which is revealed ad extra through the concrete ways in which God deals with us. Seen in this light, the exercise of divine power is intricately related to God’s nature as a faithful, loving, and free being who allows for creaturely freedom and who decides to redeem and renew rather than to coerce and obliterate.